Regenerative Medicine in Urology - Garriboli, Massimo; Radford, Anna; Southgate, Jennifer (European Journal of Pediatric Surgery, 2014)
Regenerative medicine is an emerging field that is focused on the repair, replacement or regeneration of tissues and organs. It involves multiple disciplines dedicated to delivering different aspects of the regeneration process, including cell biology, material sciences and bioengineering. The development of tissue engineering strategies incorporating the use of autologous stem cells holds particular promise for overcoming insufficiencies from using cells from the patient's own diseased tissues and providing solutions for treatment of many disorders of the genitourinary tract. Many experimental projects have successfully utilized stem cells and several pilot studies in humans indicate the potential of stem cell therapy. However, the discipline is still young and further knowledge of both materials and stem cell biology is required before this promise can be realized through clinical application. This review examines the principles related to regenerative medicine and bioengineering focusing on the stem cell isolation expansion and clinical application. Analysis of current achievements will be reviewed alongside the challenges that remain to be addressed in considering the present and future perspectives of regenerative medicine applied to urology.
Keywords: regenerative medicine; tissue engineering; stem cells; urology